Interpreting Covid-19 Pandemic Issue From Islamic Tasawwur Perspective - Beta Pujangga Mukti; Achdiar Redy Setiawan (Yayasan Rumah Peneleh, 2020)
In general, this article aims to make sense of the various discourses that have emerged around Covid-19 from the perspective of Islamic tasawwur. In Islam's religious or spiritual aspect, the Covid-19 pandemic's meaning needs to be more deeply interpreted. Thus, this essay will focus on this meaning based on Islamic tasawwur. In Islam, every Muslim believes that every event always provides a message or wisdom. Behind the